Sharing Economy in Russia: Vectors of Development of Supply Chain Management - Z. Aiusheeva, Irina; V. Soyfer, Tatiana (International Journal of Supply Chain Management, 2020)
The process of digitalization changes strategies for social intercourse organization, it predetermines the emergence of disruptive technologies and trends such as sharing economy that plays a special part among them. The purpose of the given research is to shape developments of supply chain management which will facilitate the legal framing of adequate mechanisms of relations in the sphere of shared use of goods and services (sharing economy) under growth of digital technologies. The research reviews and analyses basic ideas of economic and supply chain practices. The main research methods were deduction (specification of general principles and their application to particular spheres), induction (the study of work arrangement of certain platforms under sharing economy and further specification of general principles), and method of comparative law. Sharing economy activities may be diverse. It can be of profit-seeking or non-profit character. Thus, relations under discussion can be mediated by gratuitous and non-gratuitous contracts. Participants of sharing economy can be considered commercial and non-commercial organizations, and supply chain strategies, and it results in the necessity of solving the problem of their legal standing so that they can take part in supply chain transactions. Research findings are important for the development of legal science and supply chain in particular. On the basis of the conducted research the authors determine the main vectors of development of supply chain management to ensure evolution of sharing economy in Russia therefore, obtained results can be applied in supply chain practices, profession, and research in the sphere of economic science. The article singles out application features of supply chain frameworks with respect to the emergent economic relations. It is revealed that scientific uncertainty of the notion "sharing economy" leads to ambiguous interpretation of the legal nature of existing relations, substantial problems in applying legal standards to them, and in settlement of arising disputes. The development of sharing practices is one of the most important aims of the managers responsible for business processes management in supply chains, especially for logistics processes.